2009
DOI: 10.1186/1472-6793-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gasoline inhalation on some neurobehavioural characteristics of male rats

Abstract: BackgroundThis paper examines closely and compares the potential hazards of inhalation of two types of gasoline (car fuel). The first type is the commonly use leaded gasoline and the second is the unleaded type enriched with oxygenate additives as lead substituent in order to raise the octane number. The impacts of gasoline exposure on Na+, K+-ATPase, superoxide dismutase (SOD), acetylcholinesterase (AChE), total protein, reduced glutathione (GSH), and lipid peroxidation (TBARS) in the cerebral cortex, and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Similar results were obtained in rats treated with gasoline vapors [19], in rats treated with Nigerian Bonny light crude oil [1,2], in rats treated with cypermethrin [20] and in rats treated with Doxorubicin [21]. It was found that treating rats with crude oil was associated with anemia of the haemolytic type [18,22].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results were obtained in rats treated with gasoline vapors [19], in rats treated with Nigerian Bonny light crude oil [1,2], in rats treated with cypermethrin [20] and in rats treated with Doxorubicin [21]. It was found that treating rats with crude oil was associated with anemia of the haemolytic type [18,22].…”
Section: Discussionsupporting
confidence: 73%
“…It is used as fuel for automobiles and some electricity-generating machines [1,2]. Human population is directly or indirectly exposed to this pollutant in the course of their day-to-day activities [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the diesel exhaust particles contain ten times more extractable organic matter than the standard exhaust material generated by forklift engines. A similar type of study conducted by Kinawy (2009) revealed that the inhalation of leaded or unleaded (containing aromatics and oxygenated compounds) gasoline vapors by rats impaired the levels of monoamine neurotransmitters and other biochemical parameters in different areas of the rats' brains. Likewise, several behavioral changes causing aggression in rats were observed.…”
Section: Effects Of Petroleum Hydrocarbons On Living Mattermentioning
confidence: 97%
“…In many of these studies, biochemical markers of oxidative stress were found to increase, while antioxidant enzymes decreased significantly. Animals exposed to gasoline vapor had significantly elevated levels of lipid peroxides and a decrease in superoxide dismutase activity in brain and liver [89,90]. The underlying neuropathology associated with oxidative stress may include non-specific cell membrane interactions, leading to impaired membrane Na + /K + /ATPase activity [91] and modulation of multiple neurotransmitter systems ( Figure 5).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Kinawy [89] reported significant fluctuation in levels of monoamine neurotransmitters (dopamine, norepinephrine, and serotonin) and other biochemical parameters (sodium-potassium adenosine triphosphatase (Na + / K + /ATPase), superoxide dismutase, acetylcholinesterase (AChE), protein (Pr), GSH, lipid peroxidase) in different brain areas of animals exposed to gasoline vapor. Several reports support that induction of oxidative stress by metabolites from gasoline constituents underlies the pathogenesis of its neurotoxic effects.…”
Section: Neurotoxicitymentioning
confidence: 99%